Catch-up antibody responses and hybrid immunity in mRNA vaccinated patients at risk of severe COVID-19 - Al-Dury, Samer; Waldenström, Jesper; Ringlander, Johan; Einarsdottir, Sigrun; Andersson, Markus; Hamah Saed, Hevar; Waern, Johan; Martner, Anna; Hellstrand, Kristoffer; Lagging, Martin (Infectious diseases (London, England), 2023)
The immunogenicity of repeated vaccination and hybrid immunity in vulnerable patients remains unclear. We studied the impact of iterative Covid-19 mRNA vaccination and hybrid immunity on antibody levels in immunosuppressed subjects. Patients with liver cirrhosis ( = 38), survivors of allogeneic haematopoietic stem cell transplantation (allo-HSCT) ( = 36) and patients with autoimmune liver disease ( = 14) along with healthy controls ( = 20) were monitored for SARS-CoV-2-S1 IgG after their 1st-3rd vaccine doses, 31 of whom became infected with the Omicron variant after the 2nd dose. Ten uninfected allo-HSCT recipients received an additional 4th vaccine dose. Unexpectedly, immunosuppressed patients achieved antibody levels in parity with controls after the 3rd vaccine dose. In all study cohorts, hybrid immunity (effect of vaccination and natural infection) resulted in approximately 10-fold higher antibody levels than vaccine-induced immunity alone. Three doses of the Covid-19 mRNA vaccine entailed high antibody concentrations even in immunocompromised individuals, and hybrid-immunity resulted further augmented levels than vaccination alone. EudraCT 2021-000349-42.